Enhancing Public Health Outcomes Through Community-Based Preventive Strategies and Policy Interventions - Najihah, Khoirotun; Salmira, Cut Saura; Apriani, Nurlia (Journal of Asian-african Focus in Health, 2025)
The research examines the success rate of preventive approaches performed by communities together with policy developments which boost public health results. We used qualitative research methods to execute interviews with community members as well as health workers and policymakers who let us understand the effects of community health initiatives alongside state policies on public health delivery. Community-directed prevention interventions such as vaccine rollout and sanitation methods and health awareness programs delivered substantial health benefits that specifically reached communities without enough healthcare access. These programs-maintained sustainability only when funding was steady and both communities possessed sufficient capacity and government officials supported their actions. Policy interventions serve as fundamental components for expanding and keeping these initiatives sustainable because government financial aid together with infrastructure supplies prove essential. The research finds that implementation gaps produce difficulties because policies tend to fail in execution because bureaucracy leads to delays and insufficient community engagement and limited resources. Local needs assessment along with community involvement in developing health intervention policies would make these programs more effective and equitable according to participants. The present investigation extends present knowledge regarding health initiative sustainability over time and the need for policies that integrate community perspectives during their development process.